High-density silicon carbide composite material cladding and preparation method thereof
Patent Information
- Application Number
- CN202280100292.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-13
- Publication Date
- 2025-04-25
AI Technical Summary
It is difficult for existing SiC cladding materials to achieve meter-level thin walls and high density with ultra-aspect ratio during the preparation process, and the process cycle is long, which affects production efficiency and material performance.
The slurry is prepared using a mixture of silicon carbide fiber powder and organic solvents, dispersants, plasticizers and defoaming agents. Through molding and degreasing sintering processes, a highly dense silicon carbide shell is formed, combined with sintering aids and protective coatings. , optimizing process conditions to improve density and performance.
The preparation of high-density silicon carbide cladding with meter-level thin walls and ultra-aspect ratio has been achieved, reducing pore defects and harmful by-products, simplifying the process flow, and improving production efficiency and material performance.
Abstract
Description
High-density silicon carbide composite cladding and preparation method thereof Technical Field
[0001] The present invention relates to the technical field of nuclear fuel elements, and in particular to a high-density silicon carbide composite material cladding and a preparation method thereof. Background Art
[0002] Existing commercial Zr alloy claddings have poor high-temperature and corrosion resistance, and their high hydrogen production rate when reacting with water at high temperatures reduces the safety of nuclear power plants. SiC, with its high melting point, corrosion resistance, neutron irradiation resistance, low neutron absorption cross-section, and low hydrogen production rate when reacting with water at high temperatures, is a promising alternative to existing Zr alloy cladding materials.
[0003] At present, the preparation methods of SiC cladding materials include NITE (nano-impregnation transient liquid phase) method, CVI (chemical vapor infiltration) method, PIP (precursor impregnation pyrolysis) method and RI (reactive infiltration) method.
[0004] The NITE method for preparing SiC cladding involves impregnating SiC fibers containing an interface layer (typically pyrolyzed carbon) into a slurry composed of nano-SiC particles and an oxidative sintering aid. The mixture is then hot-pressed and sintered under an inert atmosphere (typically argon) to produce a SiC-based composite material. SiC composite cladding prepared using the NITE method exhibits advantages such as low porosity, high thermal conductivity, a dense matrix, high crystallinity, and the absence of residual Si. However, this technique requires high temperatures (≥1750°C) and high pressures (≥10 MPa), making it difficult to produce cladding materials with meter-thin walls or ultra-high aspect ratios.
[0005] The CVI / PIP method involves braiding SiC fibers containing an interface layer (typically pyrolyzed carbon) and then densifying them through the CVI / PIP process to produce SiC cladding materials. These processes can produce SiC composite claddings with meter-thin walls and ultra-high aspect ratios. However, the resulting claddings exhibit numerous pore defects, and the PIP process is lengthy.
[0006] The RI method proposes a reactive infiltration process to prepare continuous fiber reinforced SiC-based composites. The SiC cladding prepared by this process contains a lot of residual Si, which reduces its high-temperature performance and corrosion resistance.
[0007] Based on the above background requirements, it is very necessary to develop a technology that can not only realize the preparation of thin-walled, ultra-aspect ratio SiC cladding, but also ensure its high density, low residual silicon and other characteristics; considering the large-scale demand for SiC cladding, it is necessary to improve the production efficiency of SiC cladding, that is, to reduce the process cycle of SiC cladding materials. Technical issues
[0008] The technical problem to be solved by the present invention is to provide a method for preparing a high-density silicon carbide composite material cladding and the prepared silicon carbide composite material cladding. Technical Solutions
[0009] The technical solution adopted by the present invention to solve the technical problem is: to provide a method for preparing a high-density silicon carbide composite material cladding, comprising the following steps:
[0010] S1. Prepare a slurry; the slurry includes the following raw materials and their weight proportions: 45-89.7 parts of silicon carbide fiber powder mixture, 10-40 parts of organic solvent, 0.1-5 parts of dispersant, 0.1-5 parts of plasticizer and 0.1-5 parts of defoaming agent;
[0011] S2, processing the slurry into a silicon carbide cladding green body;
[0012] S3, degreasing and sintering the silicon carbide cladding green body to form a highly dense silicon carbide cladding.
[0013] Preferably, in step S1, the silicon carbide fiber powder mixture includes silicon carbide material;
[0014] The silicon carbide material comprises silicon carbide fibers and silicon carbide powder, wherein the volume percentage of the silicon carbide fibers in the silicon carbide material is 10 to 50%;
[0015] The diameter of the silicon carbide fiber is 0.01 μm to 10 μm, and the aspect ratio of the silicon carbide fiber is 10 to 1000.
[0016] Preferably, the silicon carbide fiber powder mixture further includes a sintering aid.
[0017] Preferably, the mass percentage of the sintering aid in the silicon carbide fiber powder mixture is 1 to 10%.
[0018] Preferably, the sintering aid is Al2O3-Re2O3, wherein Re is Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb or Lu.
[0019] Preferably, in the sintering aid, the ratio of Al2O3 to Re2O3 is 1wt% to 99wt%: 99wt% to 1wt%.
[0020] Preferably, in step S1, the organic solvent is at least one of anhydrous ethanol, acetone, xylene, and polyethylene glycol.
[0021] Preferably, the dispersant is at least one of oleic acid, stearic acid, and castor oil.
[0022] Preferably, the plasticizer is at least one of carboxymethyl cellulose, phenolic resin, and tetramethylammonium hydroxide.
[0023] Preferably, the defoaming agent is at least one of ethylene glycol, glycerin, and dimethyl silicone oil.
[0024] Preferably, in step S1, the raw materials are made into slurry by at least one of roller ball milling, planetary ball milling, magnetic stirring, and mechanical stirring.
[0025] Preferably, in step S2, the slurry is formed into a silicon carbide cladding green body by compression molding or extrusion molding.
[0026] Preferably, in step S3, the degreasing treatment is as follows: under vacuum, heating to 400° C. to 800° C. at a heating rate of 1° C. / min to 10° C. / min, and keeping the temperature for 1 to 10 hours.
[0027] Preferably, in step S3, the sintering treatment is as follows: heating to 800°C-1200°C at a heating rate of 10°C / min-20°C / min; then heating to 1700°C-2200°C at a heating rate of 5°C / min-10°C / min, and keeping warm for 0.5-4h.
[0028] Preferably, in step S3, the atmosphere of the sintering treatment is vacuum, or at least one of argon, helium, and nitrogen.
[0029] Preferably, in step S2, the inner diameter of the silicon carbide green body is 6 mm to 9 mm, the outer diameter is 9.5 mm to 12 mm, and the wall thickness is 0.5 mm to 1.5 mm; and the length of the silicon carbide green body is 1000 mm to 4000 mm.
[0030] Preferably, in step S3, the formed high-density silicon carbide cladding has an inner diameter of 7 mm to 8 mm, an outer diameter of 9.5 mm to 10 mm, a wall thickness of 0.5 mm to 1 mm, and a length of 1000 mm to 4000 mm.
[0031] Preferably, the density of the silicon carbide cladding is 95-99%, and the cladding leakage rate is 10 -13 ~1×10 -10 Pa·m 3 / s, its tensile strength is 200MPa~350MPa at room temperature, and its tensile strength at a high temperature of 1200℃ is 250MPa~400MPa.
[0032] Preferably, the method for preparing the high-density silicon carbide composite cladding further comprises the following steps:
[0033] S4. Applying a protective coating on the outer surface of the silicon carbide cladding.
[0034] Preferably, the protective coating includes at least one of a silicon carbide coating, a metal chromium coating, and a high entropy coating.
[0035] The present invention also provides a high-density silicon carbide composite material cladding, which is prepared by any of the preparation methods described above. Beneficial effects
[0036] The beneficial effects of the present invention are as follows: a slurry is prepared by combining a silicon carbide fiber powder mixture with an organic solvent, and then processed into a cladding green body. Combined with degreasing and sintering treatment, a meter-grade, ultra-length-diameter-ratio silicon carbide cladding is obtained, thereby improving the density of the silicon carbide cladding, reducing pore defects and its harmful by-products; simplifying the cladding preparation process, improving production efficiency; and reducing preparation costs. Modes for Carrying Out the Invention
[0037] The method for preparing the high-density silicon carbide composite material cladding of the present invention may include the following steps:
[0038] S1. Prepare slurry.
[0039] The slurry includes the following raw materials and their mass proportions: 45 to 89.7 parts of silicon carbide fiber powder mixture, 10 to 40 parts of organic solvent, 0.1 to 5 parts of dispersant, 0.1 to 5 parts of plasticizer and 0.1 to 5 parts of defoaming agent.
[0040] The silicon carbide fiber powder mixture includes silicon carbide material and a sintering aid. The silicon carbide material may further include silicon carbide fiber and silicon carbide powder, which are mixed together, with the silicon carbide fiber accounting for 10 to 50% by volume.
[0041] In the silicon carbide fiber powder mixture, the silicon carbide fiber acts as a short fiber, playing a reinforcing role and improving the density of the prepared cladding. Preferably, the diameter of the silicon carbide fiber is 0.01µm to 10µm, and the aspect ratio of the silicon carbide fiber is 10 to 1000.
[0042] In the silicon carbide material, the mass percentage of the sintering aid is 1 to 10%. The sintering aid is Al2O3-Re2O3, with the ratio of Al2O3 to Re2O3 being 1 wt% to 99 wt%:99 wt% to 1 wt%. Wherein, Re is Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb, or Lu.
[0043] For other raw materials of the slurry, the organic solvent is selected from at least one of anhydrous ethanol, acetone, xylene, and polyethylene glycol; the dispersant is selected from at least one of oleic acid, stearic acid, and castor oil; the plasticizer is selected from at least one of carboxymethyl cellulose, phenolic resin, and tetramethylammonium hydroxide; and the defoaming agent is selected from at least one of ethylene glycol, glycerin, and dimethyl silicone oil.
[0044] When preparing the slurry, the required mass of each raw material is weighed and then mixed into the slurry by at least one of roller ball milling, planetary ball milling, magnetic stirring, and mechanical stirring.
[0045] S2. The slurry is formed into a thin-walled, ultra-long-diameter-ratio silicon carbide cladding green body by molding, extrusion or other processing methods.
[0046] Specifically, the inner diameter of the silicon carbide green body is 6 mm to 9 mm, the outer diameter is 9.5 mm to 12 mm, and the wall thickness is 0.5 mm to 1.5 mm; the length of the silicon carbide green body is 1000 mm to 4000 mm.
[0047] S3. Degreasing and sintering the silicon carbide cladding green body to form a highly dense silicon carbide cladding.
[0048] The degreasing treatment is as follows: under vacuum, heating to 400°C to 800°C at a heating rate of 1°C / min to 10°C / min, and keeping the temperature for 1 to 10 hours.
[0049] The sintering process is as follows: heating the temperature to 800°C to 1200°C at a heating rate of 10°C / min to 20°C / min; then heating the temperature to 1700°C to 2200°C at a heating rate of 5°C / min to 10°C / min, and holding the temperature for 0.5 to 4 hours. The sintering atmosphere is vacuum, or at least one of argon, helium, and nitrogen.
[0050] After degreasing and sintering, the formed high-density silicon carbide cladding has an inner diameter of 7mm to 8mm, an outer diameter of 9.5mm to 10mm, a wall thickness of 0.5mm to 1mm, and a length of 1000mm to 4000mm.
[0051] S4. Protective coating on the outer surface of the silicon carbide cladding.
[0052] The corrosion resistance of the silicon carbide cladding is improved by providing a protective coating. The protective coating includes at least one of a silicon carbide coating, a metal chromium coating, and a high entropy coating, and the protective coating is preferably a metal chromium coating.
[0053] The silicon carbide composite material cladding prepared by the present invention has a density of 95-99% and a cladding leakage rate of 10 -13 ~1×10 -10 Pa·m 3 / s, its tensile strength is 200MPa~350MPa at room temperature, and its tensile strength at a high temperature of 1200℃ is 250MPa~400MPa.
[0054] The present invention will be further described below by means of specific examples.
[0055] Example 1
[0056] The slurry consists of an 80wt% silicon carbide fiber powder mixture, 10wt% organic solvent, 2.5wt% dispersant, 5wt% plasticizer, and 2.5wt% defoamer. The dispersant is oleic acid, the plasticizer is carboxymethyl cellulose, the defoamer is ethylene glycol, and the organic solvent is anhydrous ethanol. The sintering aid in the silicon carbide fiber powder mixture is 10%, and the sintering aid is Al2O3-Y2O3, with a ratio of Al2O3 to Y2O3 of 45wt%:55wt%. The silicon carbide material comprises silicon carbide fiber and silicon carbide powder, with a volume ratio of 40%, a silicon carbide fiber diameter of 0.1 µm, and an aspect ratio of 500. The above ingredients were mixed using a roller ball mill using silicon nitride balls and anhydrous ethanol as the milling medium to prepare the slurry.
[0057] The slurry was extruded into a green cladding with an inner diameter of 7.9 mm, an outer diameter of 10 mm, a wall thickness of 1.05 mm, and a length of 4000 mm. Debinding was performed under vacuum by heating the material to 600°C at a rate of 2°C / min and holding for 5 hours. After debinding, the material was sintered at a rate of 10°C / min to 1200°C, then to 1900°C at a rate of 5°C / min and held for 2 hours in an argon atmosphere. After sintering, a dense silicon carbide composite cladding with an inner diameter of 8.0 mm, an outer diameter of 10.0 mm, a wall thickness of 1.0 mm, and a length of 4000 mm was formed.
[0058] The density of the silicon carbide composite cladding prepared in this embodiment is 99%, and the cladding leakage rate is 10 -13 Pa·m 3 / s, its tensile strength at room temperature is 300 MPa, and its tensile strength at a high temperature of 1200℃ is 350 MPa.
[0059] Example 2
[0060] The slurry raw materials included: 89.7 wt% silicon carbide fiber powder mixture, 10 wt% organic solvent, 0.1 wt% dispersant, 0.1 wt% plasticizer, and 0.1 wt% defoamer; the volume ratio of silicon carbide fiber in the silicon carbide fiber powder mixture was 10%, the silicon carbide fiber diameter was 0.01 µm, and the fiber aspect ratio was 1000. The remaining steps were the same as in Example 1 to prepare a slurry.
[0061] The slurry was extruded into a green cladding with an inner diameter of 7.9 mm, an outer diameter of 9.5 mm, a wall thickness of 0.8 mm, and a length of 4000 mm. Debinding was performed under vacuum by heating the material to 500°C at a rate of 2°C / min and holding for 2 hours. After debinding, the material was sintered at a rate of 10°C / min to 1200°C, then to 1800°C at a rate of 5°C / min and held for 2 hours in an argon atmosphere. After sintering, a dense silicon carbide composite cladding with an inner diameter of 7.95 mm, an outer diameter of 9.5 mm, a wall thickness of 0.775 mm, and a length of 4000 mm was formed.
[0062] The density of the silicon carbide composite cladding prepared in this embodiment is 99%, and the cladding leakage rate is 10 -12 Pa·m 3 / s, its tensile strength is 350 MPa at room temperature and 400 MPa at a high temperature of 1200℃.
[0063] Example 3
[0064] The slurry raw materials include: 50 wt% silicon carbide fiber powder mixture, 40 wt% organic solvent, 2.5 wt% dispersant, 3.5 wt% plasticizer, and 4.0 wt% defoamer; the volume ratio of silicon carbide fiber in the silicon carbide fiber powder mixture is 50%, the silicon carbide fiber diameter is 1 µm, and the fiber aspect ratio is 10. The remaining steps are the same as in Example 1 to prepare a slurry.
[0065] The slurry was extruded into a green cladding with an inner diameter of 8.2 mm, an outer diameter of 11.0 mm, a wall thickness of 1.4 mm, and a length of 4000 mm. Debinding was performed under vacuum by heating the material to 800°C at a rate of 2°C / min and holding the temperature for 10 hours. After debinding, the material was sintered at a rate of 10°C / min to 1200°C, then to 2200°C at a rate of 5°C / min and held for 2 hours in an argon atmosphere. After sintering, a dense silicon carbide composite cladding with an inner diameter of 7.9 mm, an outer diameter of 9.9 mm, a wall thickness of 1.0 mm, and a length of 4000 mm was formed.
[0066] The density of the silicon carbide composite cladding prepared in this embodiment is 99%, and the cladding leakage rate is 10 -13 Pa·m 3 / s, its tensile strength is 350 MPa at room temperature and 400 MPa at a high temperature of 1200℃.
[0067] Example 4
[0068] The slurry raw materials included: 70 wt% silicon carbide fiber powder mixture, 20 wt% organic solvent, 3.5 wt% dispersant, 3.5 wt% plasticizer, and 3.0 wt% defoamer; the volume ratio of silicon carbide fiber in the silicon carbide fiber powder mixture was 35%, the silicon carbide fiber diameter was 5 µm, and the fiber aspect ratio was 10. The remaining steps were the same as in Example 1 to prepare a slurry.
[0069] The above slurry was extruded into a cladding green body with an inner diameter of 8.1 mm, an outer diameter of 10.1 mm, a wall thickness of 1.0 mm, and a length of 4000 mm. Degreasing was performed under a vacuum environment, with the temperature rising to 600°C at a rate of 2°C / min and holding for 3 hours. After degreasing, high-temperature sintering was continued, with the temperature rising to 1200°C at a rate of 10°C / min, and then to 1850°C at a rate of 5°C / min and holding for 2 hours in an argon atmosphere. After sintering, a dense silicon carbide composite cladding was formed, with an inner diameter of 8.0 mm, an outer diameter of 9.8 mm, a wall thickness of 0.9 mm, and a length of 4000 mm.
[0070] The density of the silicon carbide composite cladding prepared in this embodiment is 99%, and the cladding leakage rate is 10 -13 Pa·m 3 / s, its tensile strength is 325 MPa at room temperature and 350 MPa at a high temperature of 1200℃.
[0071] The above descriptions are merely embodiments of the present invention and are not intended to limit the patent scope of the present invention. Any equivalent structure or equivalent process transformation made using the contents of the present invention specification, or directly or indirectly applied in other related technical fields, are also included in the patent protection scope of the present invention.
Claims
1. A method for preparing a high-density silicon carbide composite cladding, characterized in that: The following steps are involved: S1. Prepare a slurry; the slurry includes the following raw materials and their weight proportions: 45-89.7 parts of silicon carbide fiber powder mixture, 10-40 parts of organic solvent, 0.1-5 parts of dispersant, 0.1-5 parts of plasticizer and 0.1-5 parts of defoaming agent; S2, processing the slurry into a silicon carbide cladding green body; S3, degreasing and sintering the silicon carbide cladding green body to form a highly dense silicon carbide cladding.
2. The method for preparing a high-density silicon carbide composite cladding according to claim 1, characterized in that: In step S1, the silicon carbide fiber powder mixture includes silicon carbide material; The silicon carbide material comprises silicon carbide fibers and silicon carbide powder, wherein the volume percentage of the silicon carbide fibers in the silicon carbide material is 10 to 50%; The diameter of the silicon carbide fiber is 0.01 μm to 10 μm, and the aspect ratio of the silicon carbide fiber is 10 to 1000.
3. The method for preparing a high-density silicon carbide composite cladding according to claim 2, characterized in that: The silicon carbide fiber powder mixture also includes a sintering aid; The mass percentage of the sintering aid in the silicon carbide fiber powder mixture is 1 to 10%.
4. The method for preparing a high-density silicon carbide composite cladding according to claim 3, characterized in that: The sintering aid is Al2O3-Re2O3, wherein Re is Sc, Y, La, Ce, Pr, Nd, Pm, Sm, Eu, Gd, Tb, Dy, Ho, Er, Tm, Yb or Lu; In the sintering aid, the ratio of Al2O3 to Re2O3 is 1wt% to 99wt%: 99wt% to 1wt%.
5. The method for preparing a high-density silicon carbide composite cladding according to claim 1, characterized in that: In step S1, the organic solvent is at least one of anhydrous ethanol, acetone, xylene, and polyethylene glycol; The dispersant is at least one of oleic acid, stearic acid, and castor oil; The plasticizer is at least one of carboxymethyl cellulose, phenolic resin, and tetramethylammonium hydroxide; The defoaming agent is at least one of ethylene glycol, glycerin and dimethyl silicone oil.
6. The method for preparing a high-density silicon carbide composite cladding according to claim 1, characterized in that: In step S1, the raw materials are made into slurry by at least one of roller ball milling, planetary ball milling, magnetic stirring, and mechanical stirring.
7. The method for preparing a high-density silicon carbide composite cladding according to claim 1, characterized in that: In step S2, the slurry is formed into a silicon carbide cladding green body by compression molding or extrusion molding.
8. The method for preparing a high-density silicon carbide composite cladding according to claim 1, characterized in that: In step S3, the degreasing treatment is as follows: under vacuum, the temperature is increased to 400° C. to 800° C. at a heating rate of 1° C. / min to 10° C. / min, and the temperature is kept for 1 to 10 hours.
9. The method for preparing a high-density silicon carbide composite cladding according to claim 1, characterized in that: In step S3, the sintering treatment is as follows: heating to 800°C to 1200°C at a heating rate of 10°C / min to 20°C / min; then heating to 1700°C to 2200°C at a heating rate of 5°C / min to 10°C / min, and keeping the temperature for 0.5 to 4 hours.
10. The method for preparing a high-density silicon carbide composite cladding according to claim 1, characterized in that: In step S3, the sintering atmosphere is vacuum, or at least one of argon, helium, and nitrogen.
11. The method for preparing a high-density silicon carbide composite cladding according to any one of claims 1 to 10, characterized in that: In step S2, the inner diameter of the silicon carbide green body is 6 mm to 9 mm, the outer diameter is 9.5 mm to 12 mm, and the wall thickness is 0.5 mm to 1.5 mm; the length of the silicon carbide green body is 1000 mm to 4000 mm.
12. The method for preparing a high-density silicon carbide composite cladding according to claim 11, characterized in that: In step S3 , the formed high-density silicon carbide cladding has an inner diameter of 7 mm to 8 mm, an outer diameter of 9.5 mm to 10 mm, a wall thickness of 0.5 mm to 1 mm, and a length of 1000 mm to 4000 mm.
13. The method for preparing a high-density silicon carbide composite cladding according to any one of claims 1 to 10, characterized in that: The density of the silicon carbide cladding is 95-99%, and the cladding leakage rate is 10 -13 ~1×10 -10 Pa·m 3 / s, its tensile strength is 200MPa~350MPa at room temperature, and its tensile strength at a high temperature of 1200℃ is 250MPa~400MPa.
14. The method for preparing a high-density silicon carbide composite cladding according to any one of claims 1 to 10, characterized in that: The method for preparing the high-density silicon carbide composite material cladding further comprises the following steps: S4. Applying a protective coating on the outer surface of the silicon carbide cladding.
15. The method for preparing a high-density silicon carbide composite cladding according to claim 14, characterized in that: The protective coating includes at least one of a silicon carbide coating, a metal chromium coating, and a high entropy coating.
16. A high-density silicon carbide composite cladding, characterized in that: The method is prepared according to any one of claims 1 to 15.
Citation Information
Patent Citations
SiC staple fiber composite, composite cladding tube and preparation method of composite cladding tube
CN106904984A
High-strength and high-toughness silicon carbide fiber reinforced silicon carbide ceramic-based composite material preparation method
CN106977217A
MAX phase ceramic pipe and preparation method thereof as well as nuclear fuel cladding tube
CN108147828A
Preparation method of high-compactness SiCf / SiC cladding composite pipe
CN112374902A
Thin-wall silicon carbide ceramic heat exchange tube, and preparation method and application thereof
CN113563082A